Epidemiology and Antibiotic Resistance Pattern of Prosthetic Joint Infections: A Cross-Sectional Study - T. Ashita Singh; K. Jaya Krishna Singh, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: One of the most dangerous side effects after joint arthroplasty is prosthetic joint infections (PJIs), which raise morbidity, hospital stays, and medical expenses. Optimising empirical therapy requires an understanding of epidemiology and trends in antimicrobial resistance (AMR). Objectives: To evaluate the demographic profile, microbiological etiology, and antimicrobial resistance patterns among patients with PJIs. Methods: This cross-sectional study included 98 patients diagnosed with PJIs at MediCiti Institute of Medical Sciences, Medchal, from January 2024 to December 2024. Microbiological cultures were performed, and isolates were tested for antimicrobial susceptibility. Results: The mean age was 64.5 ± 10.3 years, with a male-to-female ratio of 1.4:1. The most commonly infected joint was the knee (58.2%), followed by the hip (35.7%). The leading causative organisms were Staphylococcus aureus (43.9%, of which 58.1% were MRSA), Coagulase-negative staphylococci (CoNS, 26.5%), and Gram-negative bacilli (21.4%). High resistance was observed to penicillin (87.2%) and ciprofloxacin (69.2%), while linezolid and vancomycin retained good activity. Among Gram-negatives, Pseudomonas aeruginosa and Klebsiella pneumoniae showed high resistance to cephalosporins and fluoroquinolones. Conclusion: PJIs at our institution are predominantly caused by Gram-positive cocci, particularly MRSA and CoNS, with worrying antimicrobial resistance trends. Routine local surveillance and antibiotic stewardship are essential to guide empirical therapy.